2020
DOI: 10.1002/btpr.2993
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic model of pH and excipient concentration during ultrafiltration and diafiltration processes of therapeutic antibodies

Abstract: Ultrafiltration and diafiltration (UF/DF) unit operations are widely used for the manufacture of therapeutic antibodies to control drug substance protein concentration, pH, and excipient properties. During UF/DF, molecular interactions and volume

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Equivalence between a process model and its respective full‐scale unit operation is the fundamental requirement for applying the model to process characterization studies in late stage DSP development. The TOST is currently the state of the art equivalence testing approach for SDM qualification 15,23 . In Figure 5, the in silico model was qualified against manufacturing‐scale data using the TOST qualification scheme described in section 3.2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equivalence between a process model and its respective full‐scale unit operation is the fundamental requirement for applying the model to process characterization studies in late stage DSP development. The TOST is currently the state of the art equivalence testing approach for SDM qualification 15,23 . In Figure 5, the in silico model was qualified against manufacturing‐scale data using the TOST qualification scheme described in section 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mechanistic model simulations considered the variability in the input material, loading density and mobile phase properties for each of the chromatographic cycles. Experimental SDM and mechanistic model were qualified against large‐scale data using the identical equivalence testing procedure 15,23 Step 1‐ Calculation of the equivalence acceptance criteria (EAC) based on the sample mean ± 3 standard deviations ( SD ) of historical large‐scale runs. Step 2‐ Equivalence test: A TOST was performed according to Schuirmann 48 using Python 3.8.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Process and product‐related impurities are removed during downstream purification followed by the ultrafiltration and diafiltration (UF/DF) step to generate the drug substance. During a UF/DF operation, diafiltration (DF) is used to buffer exchange the protein from its initial composition into the final formulation composition and pH, while ultrafiltration (UF) is used to concentrate the solution to the desired protein concentration (Ladwig, Zhu, Rolandi, Hart, & Rydholm, 2020; Stoner et al, 2004). The design of UF/DF operations to achieve the target final formulation conditions often presents unique challenges at high concentrations as proteins and excipients tend to interact significantly to cause exclusion effects (Bolton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, dynamic mathematical UF/DF models based on Nernst-Planck and Poisson-Boltzmann equations were developed (Hebbi et al, 2020;Ladwig et al, 2020). Hebbi et al (2020) focused on the interaction between mAb and monovalent ions on a membrane, by assuming constant feed tank formulation, while Ladwig et al (2020) focused on the simulation of pH and excipient conditions in retentate pools. Although all later studies showed promising industrial potential, they do not consider the effect of pH and salt concentration on a protein net charge.…”
Section: Introductionmentioning
confidence: 99%